An Analysis of Causal Relationship between Remittances and Imports in Nepal - Phaju, Rajan (Economic Journal of Nepal, 2021)
The study aims to evaluate the casual relationship between remittances and imports in Nepal. Remittances are considered to be the most significant source of foreign currency that makes strong position of balance of payments, whereas the volume of imports is one of the most significant elements that lowers the volume of foreign currency reserve of the nation. It is generally believed that remittances have positive effects on volume of imports. On the contrary, if there is more imports than exports, it may run out trade deficit. It does make negative impact on the exchange rate of the home country. A weaker currency can raise the value of remittances sent back to the country, encouraging migrants to send more money home that influenced in growth of remittance. To analyze the relationship between remittance and imports, the study used annual data for 46 years from 1975 to 2020 A.D. The study used Vector Autoregressive model as there is no co-integration between the variables as per Johansen’s technique. The variance decomposition test is carried out in a similar manner. The results demonstrate that there is a close connection between remittances and imports. But surprisingly, the result of VAR Granger causality test reveals that imports cause remittance rather than the other way around. Since import influences remittances, policymakers should consider enacting policies that discourage import and encourage export.